Photothermal-controlled microneedle for transdermal delivery of metal-phenolic nanozyme with staged multifunctions to accelerate healing of infected diabetic wounds - Yan, Dong; Cao, Guoqi; Gao, Yikai; Wang, Yiping; Zhang, Wenqiang; Wang, Kun; Mao, Shumei; Li, Chengde; Zhou, Guangdong; Xia, Huitang; Dai, Wufei; Yan, Xiaoyu; et al. (Materials Today Bio, 2025)
Conventional wound dressings for infected diabetic wounds (IDWs) typically target only the wound surface, often neglecting the need for multifunctional therapies that address deeper tissue layers, resulting in less effective treatment outcomes. Emerging research suggests that a comprehensive approach to IDW therapy should involve the transdermal delivery of therapeutic agents capable of staged bacterial eradication, reactive oxygen species (ROS) scavenging, and angiogenesis. This study introduces a novel metal-phenolic nanozyme, CuTA@MnO2 nanoflake, designed for transdermal delivery in IDW therapy. The nanozyme is synthesized by loading copper ions (Cu2+) onto manganese dioxide (MnO2) via in-situ polymerization, with tannic acid (TA) as a linker, and encapsulated in a hyaluronic acid (HA) solution to form a photothermally controlled microneedle system. In a IDW rat model, this system effectively delivered photothermal therapy, eliminating bacteria under 808 nm near-infrared light. The heat-induced HA degradation released the CuTA@MnO2 nanoflake, where MnO2 and TA reduced ROS levels, providing antioxidant effects. Concurrently, released Cu2+ promoted angiogenesis, significantly accelerating wound healing. Whole transcriptome RNA sequencing confirmed that the CuTA@MnO2 microneedle enhanced angiogenesis and collagen remodeling, along with reduced inflammation. The CuTA@MnO2 microneedle offers a promising platform for the staged treatment of IDWs through bacterial eradication, oxidant scavenging, and angiogenesis promotion.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Metal-phenolic nanozyme; Photothermal-controllable; Staged multifunction; Transdermal delivery; Wound healing